Long‐Term Highly Stable High‐Voltage LiCoO2 Synthesized via a Solid Sulfur‐Assisted One‐Pot Approach. Issue 26 (2nd June 2022) - Tan, Xinghua; Mao, Dongdong; Zhao, Tingqiao; Zhang, Yongxin; Song, Luting; Fan, Zhengwei; Liu, Guangyao; Wang, Hanfu; Chu, Weiguo
Abstract: Commercialized lithium cobalt oxide (LCO) only shows a relatively low capacity of ≈ 175 mAh g −1 despite a high theoretical capacity of ≈ 274 mAh g −1 . As an effective and direct strategy, increasing its charge cutoff voltage can, in principle, escalate the capacity, which is however precluded by the irreversible phase transition, oxygen loss, and severe side reactions with electrolytes normally. Herein, an in situ sulfur‐assisted solid‐state approach is proposed for one‐pot synthesis of long‐term highly stable high‐voltage LCO with a novel compound structure. The coating of coherent spinel Lix Co2 O4 shells on and the gradient doping of SO4 2− polyanions into LCO are in situ realized simultaneously in terms of gas–solid interface reactions between metal oxides and generated SO2 gas from sulfur during synthesis. At 4.6 V, this LCO shows the discharge capacities of 232.4 mAh g −1 at 0.1 C (1 C =  280 mA g− 1 ), 215 mAh g −1 at 1 C and 139 mAh g −1 even at 20 C and the capacity retentions of 97.4% (89.7%) after 100 (300) cycles at 1 C. This approach is facile, low‐cost and up‐scalable and may provide a route to improve the performance of LCO and other electrode materials greatly. Abstract : A strategy is developed for simultaneous realization of spinel‐Lix Co2 O4 coherent coatings on and SO4 2− ‐polyanion gradient doping into LiCoO2 via gas‐solid interfacial reactions between metal oxides and in situ generated SO2 from sulfur added during one‐pot synthesis. This strategy is facile, cost‐effective, and up‐scalable. The LiCoO2 with this compound structure exhibits superior electrochemical performances at 4.6 V.